Conceptualizing and measuring strategy implementation: A multidimensional view. (19th November 2019) - Amoo, Nii; Hiddlestone‐Mumford, Jacqueline; Ruzibuka, John; Akwei, Cynthia
Abstract: When it comes to strategy making and strategy implementation, although it is acknowledged that the biggest challenge is the implementation, most of the literature tends to focus more on the strategy making part. Just like how the strategy implementation part of the strategy process has received little attention in the strategic planning literature, equally there are not much research devoted to developing measures for studying this important management process and practice. Through quantitative methodological approaches for studying the strategic management and planning process, and analysis of data from 208 senior managers involved in strategy processes within ten UK industrial sectors, this paper addresses this void by presenting evidence on the measurement properties of a multi‐dimensional instrument that assesses ten dimensions of strategy implementation. Using exploratory factor analysis, results indicate the sub‐constructs (the ten dimensions) are uni‐dimensional factors with acceptable reliability and validity. Furthermore, using three additional measures, a correlation and hierarchical regression analysis, the nomological validity for the multi‐dimensional strategy implementation construct was also established. Relative importance of ten strategy implementation dimensions (activities) for practising managers is highlighted, with the mutually and combinative effects and drawing conclusion that senior management involvement leads the way among the ten key identified activities vital for successful strategy implementation.